2021
DOI: 10.1021/acsomega.1c02173
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Carbonization of Searsia lancea Trees Grown on Mine Drainage: Processing Variables and Product Composition

Abstract: A 12-year-old planted woodlands Searsia lancea tree, grown on acid mine drainage for phytoremediation of polluted groundwater on gold and uranium mines in South Africa, was used in this research. The research describes the fuel-related characteristics and the influence of different operating conditions on the hydrothermal carbonization of the biomass and the combustion profiles of discard coal/biomass hydrochar pellets. The raw biomass was treated at temperatures ranging from 200−280 °C and residence time of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(80 reference statements)
1
5
0
Order By: Relevance
“…The physicochemical results reported for the untreated biomass used in this study are similar to those reported by Setepu et al, 25 with the inherent moisture of 8.01%. The high moisture content in biomass could make it more liable to SPONCOM.…”
Section: Relationship Between the Physicochemical Properties Of Bioma...supporting
confidence: 89%
“…The physicochemical results reported for the untreated biomass used in this study are similar to those reported by Setepu et al, 25 with the inherent moisture of 8.01%. The high moisture content in biomass could make it more liable to SPONCOM.…”
Section: Relationship Between the Physicochemical Properties Of Bioma...supporting
confidence: 89%
“…All the pellets produced at the two different blending ratios were subjected to proximate analysis, calorific value, and various mechanical tests. The results obtained from the combustion and chemical elemental composition of the pellet samples were reported previously (Setsepu et al, 2021).…”
Section: Hydrochar Production and Pelletizationmentioning
confidence: 63%
“…MLR and PLSR are both linear regression models, where PLSR models are able to resolve the colinearity among the input variables and provide unbiased input-output relationships . On the contrary, MPR is nonlinear in nature and typically represents a second- or third-order polynomial regression model in the RRCC literature. The outputs of MPR are further utilized for process optimization through response surface methodology. Among ML models, ANNs are black-box models that mimic biological neurons by attempting to replicate information transfer between biological neurons through electrical signals using mathematical functions. , ANN models have been highly successful in combining complex nonlinear input data to predict outputs .…”
Section: Methodsmentioning
confidence: 99%